2018
DOI: 10.1111/famp.12373
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Coparenting, Parenting Stress, Harsh Parenting, and Child Behavior Problems in Nonmarital Families

Abstract: Supportive coparenting is an identified protective factor for child development and behavioral outcomes. What is less known is how supportive coparenting dynamically links with other aspects of parenting and parent well-being, particularly in multi-stressed nonmarital families. This study used data from the Fragile Families and Child Wellbeing study, analyzed within a structural equation model, to explore how mothers' experience of maternal depression, maternal age, father education, and SES interacted with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 61 publications
9
73
1
5
Order By: Relevance
“…Positivity in the coparenting relationship (residential and not) and constructive communication are associated with fewer behavior problems in children and adolescents, both concurrently and over time (Knopp et al, ; Teubert & Pinquart, ). Using data from the Fragile Families and Child Wellbeing study, for example, Choi and Becher () found supportive coparenting (i.e., communicating affirmation, appreciation, and respect for one another's parenting) when children were about age 5 was associated with fewer behavior problems 4 years later. This association provided support for a compensatory resiliency process because parents' harsh parenting at age 9 was controlled in the analysis.…”
Section: Strengths In Familiesmentioning
confidence: 99%
“…Positivity in the coparenting relationship (residential and not) and constructive communication are associated with fewer behavior problems in children and adolescents, both concurrently and over time (Knopp et al, ; Teubert & Pinquart, ). Using data from the Fragile Families and Child Wellbeing study, for example, Choi and Becher () found supportive coparenting (i.e., communicating affirmation, appreciation, and respect for one another's parenting) when children were about age 5 was associated with fewer behavior problems 4 years later. This association provided support for a compensatory resiliency process because parents' harsh parenting at age 9 was controlled in the analysis.…”
Section: Strengths In Familiesmentioning
confidence: 99%
“…Older parents may also feel like the content is directed to parents of younger children. Furthermore, some evidence suggests that maternal age is positively associated with supportive co‐parenting behaviors (Choi & Becher, 2019). When paired together, these results may indicate that older adults generally have greater skills (or perceived skills) regarding co‐parenting behaviors and therefore may receive less benefit from divorce education.…”
Section: Remaining Questions and Future Directionsmentioning
confidence: 99%
“…A robust coparenting alliance is linked to positive outcomes for children (Teubert & Pinquart, 2010), and a weak coparenting alliance may be responsible for some of the negative outcomes observed in children whose parents divorce (Gasper, Stolberg, Macie, & Williams, 2008). In addition, divorce is a stressful experience for parents (Amato, 2000), and a more positive coparenting alliance can help reduce parenting stress (Choi & Becher, 2018;Cooper, McLanahan, Meadows, & Brooks-Gunn, 2009;Fagan & Lee, 2014). A weaker coparenting alliance is also associated with reduced nonresident father involvement (Ahrons & Miller, 1993), which is compounded by fewer connections for children to their extended family network through their father (Ahrons, 2007).…”
Section: Variables Of Interestmentioning
confidence: 99%
“…Theoretically, positive parenting might be associated with characteristics of the coparenting alliance and the degree or nature of coparenting conflict through a spillover effect of stress reduction along with increased positive affect and social capital (Doty, Davis, & Arditti, ). Choi and Becher () found that for single mothers in the Fragile Families and Child Wellbeing data set, more supportive coparenting was associated with less parenting stress, which dynamically predicted less harsh parenting practices and child behavior problems, indicating some relationships among these variables in addition to direct effects. Anecdotally, we often see parents put greater investment into the coparenting alliance when they are also committed to being positive parents.…”
mentioning
confidence: 99%